-31-4x=-5-(1+5x)

Simple and best practice solution for -31-4x=-5-(1+5x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -31-4x=-5-(1+5x) equation:


Simplifying
-31 + -4x = -5 + -1(1 + 5x)
-31 + -4x = -5 + (1 * -1 + 5x * -1)
-31 + -4x = -5 + (-1 + -5x)

Combine like terms: -5 + -1 = -6
-31 + -4x = -6 + -5x

Solving
-31 + -4x = -6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-31 + -4x + 5x = -6 + -5x + 5x

Combine like terms: -4x + 5x = 1x
-31 + 1x = -6 + -5x + 5x

Combine like terms: -5x + 5x = 0
-31 + 1x = -6 + 0
-31 + 1x = -6

Add '31' to each side of the equation.
-31 + 31 + 1x = -6 + 31

Combine like terms: -31 + 31 = 0
0 + 1x = -6 + 31
1x = -6 + 31

Combine like terms: -6 + 31 = 25
1x = 25

Divide each side by '1'.
x = 25

Simplifying
x = 25

See similar equations:

| (4a-3b+c-5d)5= | | 4(6t+2)=54 | | 4x+x-5=4x+4 | | 4(6t+2)=52 | | -2(21y)= | | 4(6t+2)=53 | | 4(6t+2)=60 | | -2x=-2+8 | | 5x-6=-81 | | 4(6t+2)=4 | | 5x+12-9x=19-15x+11x-7 | | 7x-6x+4x-9x= | | 9+8q=11+7q | | 4(6t+2)=50 | | 4(6t+2)=40 | | 4(6t+2)=28 | | -22(a+6)=-22 | | -3x-2=25 | | 5d-32=8 | | 4r-(-11)=87 | | x/3+4=-2 | | x^4-5x^2-36= | | 10+2(2x-3)=17-(3x-8) | | 3y+78= | | (2x+9)(x+8)=0 | | 8d-22=52 | | 2s+4.6=3s-1.2 | | 5x-32=43 | | 3(m+10)= | | 7x^2=73 | | -5600+200x=0 | | -7(z+4)+3z= |

Equations solver categories